2019
DOI: 10.1097/nan.0000000000000316
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Nurses' Use of Local Anesthetics for Venous and Arterial Access

Abstract: The use of local anesthetics to relieve pain associated with intravenous cannulation and arterial blood gas sampling is given low priority in many health institutions. This review sought to identify factors influencing nurses' use of local anesthetics for these procedures. The Database Syntax Guide for Systematic Reviewers was used; health-relevant studies were critically assessed with appropriate Critical Appraisal Skills Programme tools. Significant factors influencing the use of local anesthetics for parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
(66 reference statements)
3
7
0
Order By: Relevance
“…Most participants (about 85%) believed that doctors' orders to use LA is a factor that can facilitate its use for parenteral procedures. This finding is consistent with past literature showing that doctors' non-authorisation to use LA before parenteral procedures is a barrier to nurses' ability to provide optimal pain management (Czarnecki et al, 2011;Hudson et al, 2006;Papa and Zempsky, 2010;Alobayli, 2019). Furthermore, the path analysis showed that over 60% of nurses believed that doctors underestimate pain from IV cannulation and ABG procedures, which influenced their attitudes towards LA use.…”
Section: The Need For Doctors' Orders To Use La For Parenteral Proceduressupporting
confidence: 89%
See 4 more Smart Citations
“…Most participants (about 85%) believed that doctors' orders to use LA is a factor that can facilitate its use for parenteral procedures. This finding is consistent with past literature showing that doctors' non-authorisation to use LA before parenteral procedures is a barrier to nurses' ability to provide optimal pain management (Czarnecki et al, 2011;Hudson et al, 2006;Papa and Zempsky, 2010;Alobayli, 2019). Furthermore, the path analysis showed that over 60% of nurses believed that doctors underestimate pain from IV cannulation and ABG procedures, which influenced their attitudes towards LA use.…”
Section: The Need For Doctors' Orders To Use La For Parenteral Proceduressupporting
confidence: 89%
“…This study's findings showed that most participants viewed the cost of LA as a factor influencing its availability in the hospital. This finding is consistent with research that identified that one reason for not using topical LA (EMLA cream) (prior to parenteral procedures) was that it was very costly (Burke et al, 2011;Alobayli, 2019). Therefore, this study considers that the cost of LA is important when summarising choices for its use in parenteral procedures because it can indeed be prohibitive to its use.…”
Section: The Cost Of La Is a Factor Influencing Its Availability In Hospitalssupporting
confidence: 87%
See 3 more Smart Citations